(untitled) (Transport systems and technologies, 2021)
All elements of load-bearing metal structures of freight cars are subject to corrosion wear. In this article, a statistical analysis of corrosion wear for each element of load-bearing metal structures. Damage to load-bearing metal structures of gondola cars taking into account corrosion wear is considered. Measures to increase the possible maximum corrosion wear, which can be used to predict the residual life and structural finishing of the elements of load-bearing metal structures. Cracks and fractures that are not detected in time, which turn into through-corrosion during operation, have a great impact on corrosion. To determine the corrosion of the freight car requires an individual approach to each element of the load-bearing structures of the car, taking into account the performance and time of repair.Studies have shown that half of freight cars were operated with corrosion of some elements of load-bearing metal structures more than 30%. This shows the possibility of increasing the tolerance of the threshold of corrosion wear of cars, which will affect the ability to reduce the exclusion of freight cars from the inventory.